Deficits of social cognition in bipolar disorder: Systematic review and meta‐analysis. (8th December 2021) - Gillissie, Emily S.; Lui, Leanna M. W.; Ceban, Felicia; Miskowiak, Kamilla; Gok, Sena; Cao, Bing; Teopiz, Kayla M.; Ho, Roger; Lee, Yena; Rosenblat, Joshua D.; McIntyre, Roger S.
Abstract: Background: The association between impaired social cognition and bipolar disorder (BD) is well established. However, to our knowledge, there has not been a recent systematic review that characterizes disparate dimensions of social cognition in BD. Herein, this systematic review and meta‐analysis aimed to synthesize the literature on core aspects of social cognition (i.e., Theory of Mind, emotion recognition, and social judgment) to identify potential areas of impairment. Methods: Online databases (i.e., PubMed, Cochrane Libraries, PsycINFO) and Google Scholar were searched from inception to May 2021. Studies with populations ages ≥16 with DSM‐IV or DSM‐5 defined BD (I or II) either in a euthymic or symptomatic state were included. The risk of bias was measured using the ROBINS‐1 tool, and the quality of the sources was evaluated using GRADE criteria. The results of the studies were quantitatively measured by synthesizing Hedge's g effect sizes through a random effects meta‐analytic approach. Results: A total of 29 studies were included in the final review (i.e., 12 studies on the Theory of Mind, 11 on emotion recognition, and 6 on social judgment). Overall, results demonstrated social cognition to be moderately impaired in individuals with BD ( d = 0.59). The individual domains ranged in effect size (0.38 < d < 0.70), providing evidence for variation in impairment within social cognition. Discussion: Individuals with BD exhibit clinically significant deficits in social cognition during euthymic and symptomatic states. Social cognition impairments in individuals with BD are an important therapeutic target for treatment discovery and development.